ECONOMIC SECURITY IN BANKING SECTOR - M. Akhmadeyev; D. Shakirov (Russian Journal of Economics and Law)
Nowadays one of the most essential factors of any country's development is it security. Security issues refer to all economy sectors, including the baking sphere. Due to the dynamic growth of banking services market and information technologies the issue of security maintaining in crediting organizations becomes more topical each year. The article systematizes knowledge on defining security, gives comparative analysis of security ensuring in the USSR and Russia, views the reasons for threats formation during transition to market economy, as well as the issues of interaction between central and regional banks in the Russian Federation.